IMPACT OF THE BUSINESS ESTABLISHMENT OF PT. SURI TANI PEMUKA TO THE SOCIAL ECONOMIC OF FISHERMEN COMMUNITIES IN DOLOK PARDAMEAN SUBDISTRICT SIMALUNGUN REGENCY NORTH SUMATERA PROVINCE. - Edward G.P. Samosir; Zulkarnaini '; Hamdi Hamid (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
This research was conducted on January, 2 to 7, 2015 in the Village Tigaras Dolok Pardamean Subdistrict Simalungun Regency North Sumatera Province. The research objective was to determined the social and economic conditions of fishermen communities before and after the company PT. SURI TANI PEMUKA and the impact on the community and the area around the company establishment. Fisheries sector development PT. SURI TANI PEMUKA as part of process of local development in promoting economic growth has brought changes to the lives of the people. The changes include the impact of the company’s development of fisheries towards socio economic and environment in the area of companies especially on the fishermen.The impact of development of company PT. SURI TANI PEMUKA to the social and economic aspects, include livelihoods in fisheries and agriculture sector change to industry and trade. Other impacts to opening job opportunity for local people and migrant communities. Impact on communities in the area can lead to new businesses and increasing population to the area of the company.Keywords : business, socio – economic conditions, environmental